Pyrolyzed Substrates Induce Aromatic Compound Metabolism in the Post-fire Fungus, Pyronema domesticum - Fischer, Monika S.; Stark, Frances Grace; Berry, Timothy D.; Zeba, Nayela; Whitman, Thea; Traxler, Matthew F. (Frontiers in Microbiology, 2021)
Wildfires represent a fundamental and profound disturbance in many ecosystems, and their frequency and severity are increasing in many regions of the world. Fire affects soil by removing carbon in the form of CO2 and transforming remaining surface carbon into pyrolyzed organic material (PyOM). Fires also generate substantial necromass at depths where the heat kills soil organisms but does not catalyze the formation of PyOM. Pyronema species strongly dominate soil fungal communities within weeks to months after fire. However, the carbon pool (i.e. necromass or PyOM) that fuels their rise in abundance is unknown. We used a Pyronema domesticum isolate from the catastrophic 2013 Rim Fire (CA, USA) to ask if P. domesticum is capable of metabolizing PyOM. P. domesticum grew readily on agar media where the sole carbon source was PyOM (specifically, pine wood PyOM produced at 750 C). Using RNAseq, we investigated the response of P. domesticum to PyOM and observed a comprehensive induction of genes involved in the metabolism and mineralization of aromatic compounds, typical of those found in PyOM. Lastly, we used 13C-labeled 750 C PyOM to demonstrate that P. domesticum is capable of mineralizing PyOM to CO2. Collectively, our results indicate a robust potential for P. domesticum to liberate carbon from PyOM in post-fire ecosystems and return it to the bioavailable carbon pool.